PENGARUH PARTISIPASI ANGGARAN DAN EFEKTIVITAS PENGENDALIAN ANGGARAN TERHADAP TIMBULNYA KESENJANGAN ANGGARAN YANG DI MODERATING OLEH GAYA KEPEMIMPINAN (Studi Empiris pada SKPD di Pemerintahan Kota Pekanbaru) - Islami, Mutiara; Agusti, Restu; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study was aimed to examine the effect of budgetary participation and budget control effectiveness to budgetary slack with leadership style as moderating variable on the SKPD Government in Pekanbaru City. This study used primary data by distributing questionnaires of 73 exemplar to government officials echelon III and IV. Data collected were analyzed using multiple regression analysis and regression analysis with moderating variables. The results provide evidence that budgetary participation and budget control effectiveness effect on budgetary slack at a significance level (α) of 5%. On the other hand, the leadership style to strengthen the influence of budget control effectiveness on budgetary slack at a significance level (α) of 5%. However, the leadership style actually weaken the effect of budgetary participation on budgetary slack at a significance level (α) of 5%.Keywords: Budgetary Participation, Budget Control Effectiveness, Budgetary Slack, and Leadership Style.